2001
DOI: 10.1081/ddc-100000131
|View full text |Cite
|
Sign up to set email alerts
|

Study on Tablet Binding and Disintegrating Properties of Alternative Starches Prepared from Taro and Sweet Potato Tubers

Abstract: To demonstrate the potential alternative sources of starch used in tablet formulations, starches from taro (TS) and sweet potato (SPS) tubers were prepared with obtained yields of 11.0 and 9.6%, respectively. Both TS and SPS met USP22-NF17 identification and specifications. Their equilibrium moisture contents and gelatinization temperatures were comparable with those of commercial starch, whereas amylose contents of TS and SPS were 21.38% w/w and 41.76% w/w, respectively. Both were found to possess similar flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Small fragments of the residual granule structure are left behind in the dispersed structure matrix; these are largely composed of amylopectin and can act as structured filler particles. The amylose and amylopectin released from the granules then form a continuous gel matrix surrounding the remnants of the ruptured granules 5–7. On this basis, below a water/Na silicate ratio of 60 mL/g, complete dissolution of amylose and amylopectin takes place resulting in a continuous gel phase (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small fragments of the residual granule structure are left behind in the dispersed structure matrix; these are largely composed of amylopectin and can act as structured filler particles. The amylose and amylopectin released from the granules then form a continuous gel matrix surrounding the remnants of the ruptured granules 5–7. On this basis, below a water/Na silicate ratio of 60 mL/g, complete dissolution of amylose and amylopectin takes place resulting in a continuous gel phase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The gelatinization of starch as a multifunctional pharmaceutical excipient is most commonly achieved by heating native starch 7. It is well understood that heating causes the starch granules to swell irreversibly, leading concurrently to expansion of the amorphous regions and disruption of the crystalline regions in the granules.…”
Section: Introductionmentioning
confidence: 99%
“…It is also used in soup thickeners and baking flours, in beverages, as porridge and in producing foods for people with gastrointestinal disorders [44,[68][69][70]. Subhadhirasakul et al (2001) [71] reported that taro starch can effectively replace maize as a binding agent in tablet manufacture. Lawal (2004) [17] has suggested cocoyam starches could be modified as for other industrial starches.…”
Section: Uses Of Cocoyamsmentioning
confidence: 99%
“…The concentration of starch used is crucial; if it is below the optimum concentration then there are insufficient channels for capillary action and if it is above the optimum concentration then it is difficult to compress the compacts (Kuttke and Rudnic, 2002). As a binding agent in tablet formulations, starch is heated in solution enhancing its conversion into a paste before addition to the formula powder blend (Subhadhirasakul et al, 2001). This process is referred to as "starch pasting" or "gelatinization" whereby a substantial change in both the chemical and the physical nature of granular starch takes place.…”
Section: Introductionmentioning
confidence: 99%